The Principle and Application of "On Peak Zero" Correction in MC-ICP-MS Analysis - WANG Jin; BIAN Xiaopeng; YANG Tao (Yankuang ceshi, 2022)
BACKGROUND Multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) has been widely applied to accurate and precise measurements of isotope ratios due to its high sample throughput, strong ionization ability of ICP sources and high mass resolution. For decades, the standard-sample bracketing (SSB) method has been used to correct for instrumental mass bias during the measurement to achieve accurate results. When the content of the target isotope in samples is low, the measurement results are easily influenced by the background signals. "On Peak Zero" correction deducts the background signal from the total signal, which is an effective method to eliminate the background interference and has been widely used, but no research has been conducted to systematically explore the mathematical principles behind this correction. OBJECTIVES To establish a mathematical model for the "On Peak Zero" correction, and verify its confidence by applying it to isotope measurements of different concentrations of Li, S, Fe, Sr, Nd and Pb standard solutions. METHODS In this study, a mathematical model of the influence by the background signal on isotopic composition was established by mathematical reasoning and approximate substitution. Standard solutions of different concentrations of Li, S, Fe, Sr, Nd and Pb were prepared for the application of the "On Peak Zero" method through experimental analysis. Two types of blank signals were subtracted separately from the aggregate signals to simulate isotope measurements without and with "On Peak Zero" correction. RESULTS The results indicate that the lower the concentration of the target element, the greater is the blank solution signal influence on the accuracy of the sample to be tested, and the "On Peak Zero" method can better eliminate the influence of the blank solution on the sample measurements. The simulation results based on this model were consistent with the real experimental results in this study. CONCLUSIONS The mathematical model and the data explain well the effect of background concentration on the experimental isotope values, and are useful for understanding the application of the "On Peak Zero" method in MC-ICP-MS isotope analysis.